Tingkat Penggunaan AI Pada Mahasiswa untuk Menyelesaikan Tugas Kuliah : Perspektif Nilai-Nilai Islam - Muhammad Hendrie Fauzan; Rachel Nathania Putri; Mohammad Maliki; Catur Surya Aditama (el Buhuth: Borneo Journal of Islamic Studies, 2026)
The world of educational institutions, especially higher education, has undergone major changes as a result of advances in digital technology during the era of the 5.0 industrial revolution. Artificial Intelligence (AI) has become part of the learning process, especially in completing academic assignments. AI is one of the most widely used technological innovation tools by the current generation. The purpose of this study is to determine how many students at Semarang State University understand the use of AI and how to use it to complete college assignments, including from the perspective of Islamic values. The research data used a descriptive quantitative approach through questionnaire collection. This study used a questionnaire administered through Google Forms to collect data from each respondent. This study observed the level of AI usage by students at Semarang State University (UNNES) from batches 23, 24, and 25. The results showed that the majority of UNNES students used ChatGPT compared to other platforms. This data was collected from 50 UNNES student respondents. AI is more often used by students to search for references or summarize literature provided by lecturers, as well as to write essays or papers for course assignments. This study shows that the use of technology such as AI produces new behavior patterns in academic institutions. The use of AI cannot rely solely on technology but must be combined with Islamic values. As a result, the use of AI in completing college assignments is very high among UNNES students.